2006
DOI: 10.1111/j.1365-2036.2006.03103.x
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic sphincterotomy with or without cholecystectomy for choledocholithiasis in high‐risk surgical patients: a decision analysis

Abstract: SUMMARY BackgroundLaparoscopic cholecystectomy (LC) is recommended for patients with choledocholithiasis after ERCP with sphincterotomy (ES) and stone extraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Therefore, patients with symptomatic CBD stones and who are high operative risk [American Society of Anesthesiologists (ASA) IV, V or elderly patient over 70] may be considered for ERCP/ES without cholecystectomy. 18 Laparoscopic cholecystectomy and IOC with LCBDE, when choledocholithiasis is found without preoperative ERCP, is recommended for surgeons with the skill and facilities to do LCBDE. If surgeons are not skilled in LCBDE or practice in hospitals which cannot support LCBDE, then a Fitzgibbons tube is a good alternative.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, patients with symptomatic CBD stones and who are high operative risk [American Society of Anesthesiologists (ASA) IV, V or elderly patient over 70] may be considered for ERCP/ES without cholecystectomy. 18 Laparoscopic cholecystectomy and IOC with LCBDE, when choledocholithiasis is found without preoperative ERCP, is recommended for surgeons with the skill and facilities to do LCBDE. If surgeons are not skilled in LCBDE or practice in hospitals which cannot support LCBDE, then a Fitzgibbons tube is a good alternative.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,[10][11][12]14,[16][17][18]20,21,33 The positive IOC incidence varies and is approximately 22% and a reported incidence of negative ERCP of 55%, 80%, 84%, and 93% in patients presenting with jaundice, pancreatitis, colic, and cholecystitis, respectively, and others reporting incidence of 50-72%. 4,[7][8][9]20,21,24,30 Laparoscopic cholecystectomy with IOC carries a morbidity of more than 6% and a mortality of 0.1% (Table 2).…”
Section: Decision Treementioning
confidence: 91%
See 2 more Smart Citations
“…It should be noted that the biliary complication rate in the wait-and-see group (47%) was significantly higher when compared with other similar trials. Several other trials [28][29][30] have also suggested ES LC as treatment of choice in younger low-risk patients with choledocholithiasis.…”
Section: Discussionmentioning
confidence: 99%